2013
DOI: 10.3348/kjr.2013.14.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience Using Dynamic MRI at 3.0 Tesla for Evaluation of Soft Tissue Tumors

Abstract: ObjectiveWe aimed to evaluate the use of dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) at 3.0 T for differentiating the benign from malignant soft tissue tumors. Also we aimed to assess whether the shorter length of DCE-MRI protocols are adequate, and to evaluate the effect of temporal resolution.Materials and MethodsDynamic contrast-enhanced magnetic resonance imaging, at 3.0 T with a 1 second temporal resolution in 13 patients with pathologically confirmed soft tissue tumors, was analyzed. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Consequently, in patients with indeterminate STMs referred for biopsy, dynamic CE-MR sequences should be used, rather than static CE-MR alone. Several previous articles emphasized the role of dynamic contrast enhanced sequences to predict malignancy in STMs, [31][32][33][34][35][36] although these studies did not specifically address the "indeterminate" STM population, and none included DWI. Our data also confirm that the dynamic CE-MR sequence is an important technique to increase reader confidence for discriminating malignant and benign STMs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in patients with indeterminate STMs referred for biopsy, dynamic CE-MR sequences should be used, rather than static CE-MR alone. Several previous articles emphasized the role of dynamic contrast enhanced sequences to predict malignancy in STMs, [31][32][33][34][35][36] although these studies did not specifically address the "indeterminate" STM population, and none included DWI. Our data also confirm that the dynamic CE-MR sequence is an important technique to increase reader confidence for discriminating malignant and benign STMs.…”
Section: Discussionmentioning
confidence: 99%
“…The steepest slope graphmight help to differentiate benign and malignant soft tissue tumors. 14 A study found that the steepest slope increasefor >30% per minute was observed in 84% of malignant soft tissue tumors. 12 Malignant tumor has a high vascularization and a relatively limited interstitial space which results in a high rate of achieving the contrast-enhanced state.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that 50% of the patients with malignant soft tissue tumor had type 4 TIC, 33% had type 3 TIC, 17% had type 2 TIC patients, and no patient had type 1 and type 5 TIC. 14 High perfusion and permeability of endothelial could be reflected withhigh enhancement intensity and contrast uptake in advanced MRI.The TIC type reflects dynamic changes in blood flow and intra-tumor perfusion. The pattern on TIC could suggest the physiology of tumor tissues, where this pattern can be used to determine the angiogenesis patterns the tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast-enhanced imaging is especially useful in assessment of hematomas or hemorrhagic lesions, in which enhanced imaging allows identification of a tumor nodule that might not otherwise be identified at nonenhanced conventional imaging. Subtraction imaging is a relatively recent innovation that has received little attention in the literature (17)(18)(19); however, we find it invaluable in such cases, since this technique eliminates the possibility of misinterpreting the T1 shortening associated with hemorrhagic change as vascular enhancement (Fig 13). It is also extremely useful in patients with metal fixation, because the subtraction technique eliminates the need for fat suppression at enhanced imaging (Fig 14).…”
Section: Contrast Materialsmentioning
confidence: 98%